2019
DOI: 10.1080/23802359.2019.1681915
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome and phylogenetic analysis of the Gray’s pipefish Halicampus grayi Kaup 1856

Abstract: In the present study, the complete mitochondrial genome of H. grayi was determined and annotated. The circular mitogenome is 16,959 bp in length and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a control region. Most of the PCGs start with ATG, but CO1 begins with a GTG start codon. Phylogenetic analysis revealed that H. grayi was strictly related to network pipefish Corythoichthys flavofasciatus with 100% bootstrap support value. This work provides basic molecular information th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…For example, a paper on the complete mitochondrial genome (KJ139455) of C. flavofasciatus(Zhang et al, 2015) was based on a misidentified fish (which represents a species of the genus Halicampus), as revealed from our phylogenetic tree (FigureS1). Our results are further substantiated by the study ofChen et al (2019) on the complete mitochondrial genome of Halicampus grayi that showed high nucleotide sequence similarity (99.45%) with the mitogenome of C. flavofasciatus (KJ139455). Similarly, another study on diversity of species traits in syngnathids that used over 50 CO1 sequences of C. flavofasciatus(Zhang et al, 2017) have in reality erroneously used sequences of the genus Halicampus.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…For example, a paper on the complete mitochondrial genome (KJ139455) of C. flavofasciatus(Zhang et al, 2015) was based on a misidentified fish (which represents a species of the genus Halicampus), as revealed from our phylogenetic tree (FigureS1). Our results are further substantiated by the study ofChen et al (2019) on the complete mitochondrial genome of Halicampus grayi that showed high nucleotide sequence similarity (99.45%) with the mitogenome of C. flavofasciatus (KJ139455). Similarly, another study on diversity of species traits in syngnathids that used over 50 CO1 sequences of C. flavofasciatus(Zhang et al, 2017) have in reality erroneously used sequences of the genus Halicampus.…”
supporting
confidence: 69%
“…Our results are further substantiated by the study of Chen et al . (2019) on the complete mitochondrial genome of Halicampus grayi that showed high nucleotide sequence similarity (99.45%) with the mitogenome of C. flavofasciatus (KJ139455). Similarly, another study on diversity of species traits in syngnathids that used over 50 CO1 sequences of C. flavofasciatus (Zhang et al ., 2017) have in reality erroneously used sequences of the genus Halicampus .…”
Section: Discussionmentioning
confidence: 99%